Pendampingan Pembuatan Desain Grafis Menggunakan Aplikasi Canva Pada Siswa SMKN 1 Kramatwatu Banten - Haerani, Reni; Annas, Nafiz; Safrina, Adhelia Permata; Hidayatullah, M Wildan; Fatmawati, Eva; Tania, Shifa; Toyib, Abu; Hayatunnufus, Hayatunnufus; Yusuf, Rifki Maulana; Jaya, Nurhadi (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2024)
The graphic design mentoring program using Canva for class X of SMKN 1 Kramatwatu Banten has 149 participants from all majors. It aims to improve students' abilities in the field of graphic design. Through this training, students are expected to be able to utilize digital technology to produce creative and innovative works that are relevant to current industry needs. The method used in this program is lectures that provide material directly to partners by resource persons. This program also involves direct practice sessions guided by experienced instructors to ensure a deep understanding of the design features and techniques in Canva. Based on the results of the activities, this training and mentoring are known to be effective in improving participants' graphic design skills. This is evidenced by the results of the pre-and post-test questionnaires for the activities to determine the results of the Community Service that has been carried out. The results of this mentoring program show a significant increase in students' abilities to create attractive and professional graphic designs. In addition, students also showed an increase in creativity and confidence in expressing their ideas through visual media. Overall, this mentoring has succeeded in improving students' competence in graphic design and preparing them to face challenges in an increasingly competitive world of work.